Child protection through intercountry adoption with special reference to The Hague Convention on Protection of Children and Co-operation in Respect of Intercountry Adoption 1993 - Abd Kadir, Nadhilah; Mohd, Azizah; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah (Global Academy of Training & Research, 2015)
Objective – This paper seeks to examine the practice of intercountry adoption as prescribed in the Hague Convention on Protection of Children and Co-operation in respect of Intercountry Adoption 1993 (the Hague Convention 1993) particularly relating to its requirements and procedures. This is in order to describe the minimum safeguards provided by The Hague Convention 1993 to ensure that such adoption takes place in the child's best interests. This paper also discusses the relationship between the Hague Convention 1993 and the United Nations Convention on the Rights of the Child 1989 (CRC) relating to the position of intercountry adoption as one of the available means of child care. Methodology/Technique – This paper adopts qualitative research method. Analysis focuses on international policies provided by International Legal Frameworks that include The Hague Convention 1993 and the CRC. Findings – The Hague Convention 1993 recognizes intercountry adoption as one of the alternative care options that provides the advantage of a permanent family setting to a child whom, a suitable family is unavailable for him or her in the birth country. Accordingly, this paper suggests that family setting should be preferred over institutional setting in deciding a child’s placement. Novelty – The paper deliberates on the position of intercountry adoption at the international level as one of the alternative care options.